Semi-quantitative evaluation of Babesia bovis and B. bigemina infection levels estimated by HRM analysis - Giglioti, Rodrigo; Okino, Cintia Hiromi; Azevedo, Bianca Tainá; Wedy, Bruna Costa Rodrigues; Gutmanis, Gunta; Veríssimo, Cecília José; Katiki, Luciana Morita; Filho, Anibal Eugênio Vercesi; de Oliveira, Henrique Nunes [UNESP]; Oliveira, Márcia Cristina de Sena (Elsevier, 2021)
Bovine babesiosis is economically the most important arthropod-borne disease of cattle worldwide. The most significant damage caused by bovine babesiosis is attributed to Babesia bovis due to its higher pathogenicity. This study aimed to develop a real-time PCR method followed by HRM (high-resolution melting) analysis for the simultaneous detection of B. bovis and B. bigemina, enabling a semi-quantitative analysis of Babesia levels using a single-tube reaction. The HRM was compared with real-time PCR using species-specific hydrolysis probes. The HRM analysis allowed to differentiate both Babesia species and was sensitive in the detection and differentiation of 10% for each Babesia species in the sample. Our results suggest the use of this method to estimate the prevalence of infections by B. bovis or B. bigemina as an alternative to the methods of absolute quantification by real-time PCR since it neither requires precise estimates of the number of DNA loads nor the construction of calibration curves. The simultaneous detection of the two Babesia species can be used to characterise the infection levels in cattle populations from different geographical regions, allowing a better control of these diseases.
Keywords: Babesiosis; HRM analysis; qPCR; semi-quantification